2012
DOI: 10.1007/s00701-012-1370-9
|View full text |Cite
|
Sign up to set email alerts
|

The frontotemporal-orbitozygomatic approach: reconstructive technique and outcome

Abstract: The reconstruction after FTOZ approach is as important as the performance of the surgical technique. Attention to anatomical details and the stepwise reconstruction are a prerequisite to the successful preservation of function and cosmesis. In our series, the orbitozygomatic osteotomy did not increase surgical complications or alter cosmetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
1
29
0
3
Order By: Relevance
“…In the neurosurgery literature, a review of 75 patients who underwent pterional surgery identified two (2.6%) cases of extraocular muscle restriction and three cases (4.0%) of ptosis. 12 The true rate of neuro-ophthalmic complications following pterional craniotomy is difficult to estimate. We encountered 8 patients with diplopia and ptosis over a 15 year period, during which 980 pterional craniotomies with orbital takedown were performed by two neurosurgeons.…”
Section: Discussionmentioning
confidence: 99%
“…In the neurosurgery literature, a review of 75 patients who underwent pterional surgery identified two (2.6%) cases of extraocular muscle restriction and three cases (4.0%) of ptosis. 12 The true rate of neuro-ophthalmic complications following pterional craniotomy is difficult to estimate. We encountered 8 patients with diplopia and ptosis over a 15 year period, during which 980 pterional craniotomies with orbital takedown were performed by two neurosurgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, poor cosmetic outcomes have been described as a result of bony gaps created by osteotomies through the superior orbital ridge and body of the zygoma or sphenoid ridge resection [13]. Use of a standard craniotome results in a significant bony defect and possible risk to neural or orbital structures by direct injury, and often requires use of cranioplasty bone cement material to avoid cosmetic deformities.…”
Section: Discussionmentioning
confidence: 99%
“…The LSO approach is less traumatic, much faster, and simpler than the classic pterional approach and allows the surgeon to easily reach the sellar region [7]. The orbitozygomatic approach, also widely used and described in the context of sellar surgery in the literature [19] is, in our opinion, even more traumatic than the pterional one and needlessly extensive.…”
Section: Discussionmentioning
confidence: 99%